Integrated GPR and laser scanning of Piazza Sant’Anastasia, Rome - Pomar, Elena; Kay, Stephen; Campbell, Peter; Vuković, Krešimir (Archaeopress, 2023)
The application of non-invasive techniques for archaeological research, in particular geophysical prospection and 3D-modelling, have been at the forefront of the research conducted by the British School at Rome (BSR), in particular at the sites of Portus and San Giovanni in Laterano. The techniques have been used for the investigation of both large-scale sites as well as documenting complex buildings, in many cases as a precursor to archaeological excavations. However, when sites are embedded in a complex urban landscape, non-intrusive methods offer the only possibility for a detailed investigation of the subsurface. The survey at Piazza Sant’ Anastasia falls within this context.
Keywords: Urban Archaeology; Geophysics; Ground Penetrating Radar; Electrical Resistance Tomography; Laser-scanning; Photogammetry; Big Data; Metadata; Archival Research